Um modelo de análise de operações de mixagens com bitcoins em serviços de mistura centralizada - Costa, Rodolfo da Silva (2020)
By design, a blockchain allows anyone interested to analyze every transactions already made on the network, in addition to consulting the balance of currencies that each wallet contains, as well as any relationship that may exist between the addresses of wallets in the network. In contrast, personal financial information is sensitive data that needs privacy, and its exposure can cause discomfort to owners. Therefore, the privacy of the holders of the assets in this system resides, by design, in the pseudo-anonymity provided by the addresses of portfolios, which do not have associated personal data, only an identifying code. However, anytime a wallet address is related to a user, all of their privacy will be lost. On the other hand, seeking the right to financial secrecy and with the prospect of achieving the desired privacy at the origin of Bitcoin, a type of service is born that uses artifices such as cryptocurrency exchange and shuffling to achieve anonymity on the network. These services are called cryptocurrency mixers or cryptocurrency tumblers. The objective of this work was to develop a blockchain analysis model to assist in the process of tracking cryptocurrencies mixed by these services. To this end, tests and analysis of the shuffling patterns of four mixers that operate on the Bitcoin Blockchain were carried out and the development of a strategy for graphing the transactions involved in the shuffling. Among the conclusions obtained, even considering that some of the users of such services may have the right to anonymity and financial secrecy, in addition to the risk offered by such services, it is also clear that the existence of mixers favors the commission of tax crimes, such as money laundering. money and tax evasion, and their use to support other illegal activities. On the other hand, tools and methodologies, such as those presented in this paper, allow law enforcement, governments and other stakeholders to trace the origin of cryptocurrencies in scenarios where this is necessary.